A better understanding of the potential conflict between Christianity and homosexuality - Subhi, Nasrudin; Geelan, David; McMahon, M.; Jusoff, Kamaruzaman; Mohamad, Mohd Suhaimi; Sarnon @ Kusenin, Norulhuda; Nen, Salina; Mohd Hoesni, Suzana; Chong, Sheau Tsuey; Ibrahim, Fauziah; Alavi, Khadijah (IDOSI Publications, 2011)
Most organized religions including Christianity still regard homosexuality as being against their teachings, as sinful and contrary to scripture. Thus the matter of reconciling sexual orientation with religious and spiritual beliefs can be a very challenging and complicated process for those homosexual persons who uphold Christianity as their religion. This paper seeks to explore the potential conflict between Christianity and homosexuality faced by the respondents. A qualitative study was conducted via in-depth semi-structured interviews with purposively selected homosexual persons. The result found that a small percentage of respondents were unaffected by the potential conflict between Christianity and homosexuality. Nevertheless, the majority, eighty percent, were affected by the conflict, implying that both Christianity and homosexuality were important components of their lives. The most common personal effects of conflict between Christianity and homosexuality indentified include depression, self-blame/guilt, anxiety, suicidal ideation and alienation. Some implications for practice are presented at two few different levels: (1) mental health professionals and (2) church leaders and clergymen.